De las Juntas a la Regencia. La difícil articulación del poder en la España de 1808 - Moliner Prada, Antonio (El Colegio de México, A.C., 2008)
The 1808 political crisis in Spain, brought about by the napoleonic invasion and the “kidnapping” of the king, spurred  an important change in the structuring of power,  which passed on from town and city councils to local and provincial Juntas. The coordination for war entailed the creation of a Junta Central, which  later on  gave place to a Consejo de Regencia,  which  in turn  paved the road to the Convocatoria  de Cortes. This whole process allows a new and more representative  political regime to be born: the liberal, as apposed to the absolutism of the Ancien Régime.